In vitro propagation of Maytenus ilicifolia (Celastraceae) as potential source for antitumoral and antioxidant quinomethide triterpenes production. A rapid quantitative method for their analysis by reverse-phase high-performance liquid chromatography - Buffa Filho, Waldemar [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Vaz Pereira, Sarazete Izidia; Pereira, Ana Maria Soares; Françab, Suzelei Castro (ARKAT USA, 2004)
Cell culture of Maytenus ilicifolia were established in order to produce and to quantify the antitumoral and antioxidant quinonemethide triterpenes. In vitro calli were induced from leaf explants of native plants and cultured in semi-solid medium under controlled conditions of humidity, temperature and photoperiod. The quinonemethide triterpenes showed maximum accumulation in the logarithmic phase growth of the cell culture. A rapid, sensitive and reliable reverse-phase HPLC method was used for quantitative determination of the antitumoral and antioxidant quinonemethide triterpenes, 22β-hydroxymaytenin and maytenin in callus of Maytenus ilicifolia. Well resolved peaks with good detection response and linearity in the range 1.0 - 100 μg/mL were obtained. This quantitative work was performed by an external standard method.
Keywords: in vitro system, Celastraceae; Maytenus ilicifolia; Quantitative determination; Quinonemethide triterpenes, Reverse-phase high-performance liquid chromatography; 22beta hydroxymaytenin; antineoplastic agent; antioxidant; maytenin; maytenus ilicifolia extract; plant extract; quinone derivative; triterpene derivative; unclassified drug; bioaccumulation; Celastraceae; cell culture; drug potency; drug synthesis; explant; humidity; in vitro study; Maytenus; photosynthesis; plant cell; plant leaf; quantitative analysis; reliability; reversed phase high performance liquid chromatography; standard; technique; temperature dependence